Tecnologia de informação e comunicação no ensino médio: a utilização das unidades de ensino potencialmente significativas com experimentos visuais sobre mecânica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The study of Information and Communication Technology (ICT) and its application in teaching have given us belief that this kind of resource can improve the learning of Physics themes in High school. Using these ways to allow schools the access to experimental results involving Physics themes é the challenge of this work. From this point of view, two Potentially Meaningful Learning Units (PMLU) were built, one for Straight uniform movement and the other for variant straight uniform movement. These PMLU are focused on using videos posted (YouTube) in a Blog (Blogger, from Google) of free access for teachers and interested students in using it. Each PMLU has four class units. The purpose of this format is to suggest a method of use for these resources to the teacher, making easier access and short, and at the same time, allowing the students to explore and collect experimental data in an autonomous and creative way, stimulating them to analyze, interpret and conclude about these experimental events that does not make part in the universe of didactical books. These PMLU were applied in two different situations: on a regular class of first year of High School and in a Physics club with 9th grade students. The evaluation process with comparison among conceptual maps (diagnostical and formative) and standard tests showed clues that the significative learning occurred in both cases. Therefore, we conclude that the method in this work has resulted in being effective, making the student active subject to his own learning process, encouraging the approach on the videos from other perspectives.
Keywords: Física; mecânica clássica; experimento visuais; movimento; Physics; movement; classic physics; visual experiments; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA